Interspecific Hybridization Enhanced Tolerance to Salinity and Cadmium Stress Through Modifying Biochemical, Physiological, and Resistance Gene Levels, Especially in Polyploid Rice: A Sustainable Way for Stress-Resilient Rice - Lixia Sun; Fozia Ghouri; Jiacheng Jin; Minghui Zhong; Weicong Huang; Zijun Lu; Jinwen Wu; Xiangdong Liu; Muhammad Qasim Shahid (Rice)
Abstract Polyploid plants exhibit strong resistance to salt and cadmium (Cd) stress, which can adversely affect their growth, reducing crop quality and yield. Transcriptome analysis, antioxidant enzymatic activities, physiological measurements of reactive oxygen species, and heterosis analysis were performed on hybrids with neo-tetraploid rice and its progenitors. The results showed that diploid hybrids had fluctuating yields in early and late seasons, while tetraploid hybrids had consistent grain yield throughout. Transcriptome analysis revealed that gene expression related to sugar metabolism processes increased in tetraploid hybrids. Transcriptome analysis revealed several genes associated with heterosis and stress, including OsEAF6, which is associated with heterosis, and OsCIPK14, which is involved in defense signalling pathways. Furthermore, compared to the parents, hybrids have a much higher number of genes associated with abiotic stress. Consequently, diploid and tetraploid hybrids were treated with Cd (0 and 100 µM) and NaCl (200 mM) in the present study. Under Cd toxicity, the levels of carotenoids were reduced by 33.31% and 45.59%, while the levels of chlorophyll a declined by 16.00% and 27.81% in tetraploid and diploid hybrids, respectively, compared to the control. Tetraploid hybrids had the highest germination rate under salt stress and the lowest Cd uptake compared to diploid hybrids and their parents. In general, the activities of antioxidant enzymes exhibited a considerable drop, whereas the levels of H2O2 and MDA showed a remarkable increase in parents compared to hybrids. Under cadmium toxicity, the expression of OsERF1 in tetraploid rice was increased, and OsABCC1 and OsHMA3 were highly expressed in neo-tetraploid rice. Interspecific hybrid (indica and japonica) displayed enhanced tolerance to cadmium and salinity stress, potentially serving as a natural resource to improve rice resilience. These findings provide a basis for understanding polyploid rice’s gene expression pattern, environmental tolerance, and heterosis.